Standardization activities for multimedia communications and GII inTTC. - Iida, T. (IEEE Communications magazine)
This article provides a summary of ongoing standardization activities in the Telecommunication Technology Committee (TTC) on multimedia communications and global information infrastructure for the future global information society. Standardization activities of fora related to multimedia communications are also discussed